Implementasi Total Quality Management dalam Pengembangan Manajemen Pembelajaran Karakter Religius - Sari, Mia (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2021)
This paper presents the implementation of Total Quality Management in developing religious character learning management. Total Quality Management as an approach that emphasizes the existence of a continuous improvement effort in maximizing products, services, and human resources. Character learning based on Total Quality Management is a process of transferring, habituating, and forming character values by educators (teachers) to students, which is carried out based on the concept of Total Quality Management, namely: quality, customer satisfaction, continuous improvement, and comprehensive in all organizational components. This research is a library research using a qualitative approach. The results of this study indicate that the implementation of Total Quality Management in the development of religious character learning management is still very much needed for educational institutions, especially in the learning process.